2018
DOI: 10.2147/jir.s165172
|View full text |Cite
|
Sign up to set email alerts
|

The effect of hydroalcoholic extract of <em>Teucrium polium L.</em> on the inflammatory markers and lipid profile in hypercholesterolemic rats

Abstract: BackgroundCardiovascular diseases are among the most common causes of mortality worldwide. Therefore, it is necessary to control the risk factors of these patients. Since the level of inflammatory markers and lipid profiles has increased in cardiovascular diseases and due to the increasing role of plants in the treatment of diseases, the current study aimed to investigate the effect of hydroalcoholic extract of Teucrium polium on inflammatory markers and lipid profile in hypercholesterolemic rats.Materials and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 37 publications
0
17
0
Order By: Relevance
“…This plant can be used as a natural remedy for managing cardiovascular diseases. A study conducted by Amraei et al showed that receiving 170 mg/kg of the hydroalcoholic extract of T. polium reduces serum levels of triglycerides, LDL-cholesterol, and cholesterol and increases serum levels of HDL-cholesterol (35). In a triple-blind study conducted on 70 women aged 20 to 30, results showed that oral administration of 250 mg of T. polium capsules every 6 hours during the first three days of menstruation resulted in a significant reduction in bleeding during menstruation (36).…”
Section: Resultsmentioning
confidence: 99%
“…This plant can be used as a natural remedy for managing cardiovascular diseases. A study conducted by Amraei et al showed that receiving 170 mg/kg of the hydroalcoholic extract of T. polium reduces serum levels of triglycerides, LDL-cholesterol, and cholesterol and increases serum levels of HDL-cholesterol (35). In a triple-blind study conducted on 70 women aged 20 to 30, results showed that oral administration of 250 mg of T. polium capsules every 6 hours during the first three days of menstruation resulted in a significant reduction in bleeding during menstruation (36).…”
Section: Resultsmentioning
confidence: 99%
“…It is worth highlighting that water/ethanol is an effective solvent in extracting phytochemicals from the plant as it combines polar and medium polarity properties [ 60 ]. Thus, it appears that the anti-inflammatory effect of the extract may be due to the presence of flavonoids and phenolic compounds in the plant [ 54 , 61 ]. Cirsiliol has been reported to possess a potent and selective 5-lipoxygenase inhibitory potential that further consolidated the in silico studies [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…As shown in the results, TPE‐SLN effectively decreases the level of IL‐1b and IL‐6 in Ntra‐2 cells, which indicates the anti‐inflammatory effect of the formed nanoparticles. In some previous studies, the anti‐inflammatory effects of the T. polium have been investigated and confirmed by various methods (Amraei et al., 2018; Rahmouni et al., 2017). Similarly, in a study conducted in 2021, etofenamate and ibuprofen were loaded on SLNs to enhance the therapeutic effect in the topical treatment of inflammation and the anti‐inflammatory effect of the prepared nanoparticles was confirmed (Mancini et al., 2021).…”
Section: Discussionmentioning
confidence: 90%